3D Geological modelling of the Taupo Volcanic Zone as a foundation for a geothermal reservoir model. Issue 1 (2nd January 2018) - Milicich, Sarah D.; Pearson-Grant, Sophie C.; Alcaraz, Samantha; White, Paul A.; Tschritter, Constanze
ABSTRACT: We present a 3D hydrogeological model of the central Taupo Volcanic Zone (TVZ), including seven geothermal fields. A combination of borehole data, surface geology and structures were used to generate representative geological groups at depth. The geological units in the model area have been combined into seven hydrogeological groups based primarily on rock types with similar hydraulic characteristics, with permeabilities ranging from 9 × 10 −15 to 2 × 10 −9  m 2 . The fault structures used in the model are simplified to nine faults that are laterally extensive or host significant fluid flow. These faults, other than the caldera collapse structures, strike northeast–southwest, reflecting the dominant structural trend in the TVZ. By visualising hydrogeological groups in 3D, realistic geology and hence permeability input data can be more easily integrated into numerical fluid flow models.